Rational emotional behavior: How to reduce irrational beliefs in victims post-natural disasters - Djamaluddin, Mawardi; Umar, Suryani Hi (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2021)
Natural disasters that occur over a long period of time and the level of damage that occurs often affect the psychological condition of the individual causing individuals to experience traumatic experiences that are hard to forget. Traumatic experiences experienced as a result of natural disasters also influence one's view of the natural disaster itself. Some people may have rational views while others have irrational views. This irrational view often makes individuals feel even more traumatized by the bad experiences they have experienced. Therefore, this study aims to examine the effectiveness of rational emotive behaviour counselling in reducing irrational beliefs experienced by people experiencing natural disasters. The research method used was quantitative with an experimental design. The research subjects were earthquake victims in Tomara Village, South Halmahera Regency who had irrational beliefs in the high category based on the results of filling in data from the irrational belief scale. The results showed that rational emotive behaviour therapy counselling was effective in reducing irrational beliefs experienced by people experiencing natural disasters.